PENINGKATAN KADAR LOVASTATIN ANGKAK OLEH Monascuspurpureus KO-KULTUR DENGAN Endomycopsis burtontt - Danik D Asadayanti; B Sri Laksmi Jenie; Harsi D Kusu aningrum; Novik Nurhidayaf (Research Center for Biology-Indonesian Institute of Sciences, 2010)
Lovastatin is a bioactive material of statin groups and has been used to reduce cholesterol through inhibiting HMG Co-A reductase enzyme activities. Three indigenous strains of Monascus purpureus and three mutans were used in this study produced lovastatin at the range of 0,1 - 1,42%. The objectives of this study were to increase lovastatin productions by co-cultured with several concentrations of Endomycopsis burtonii. M. purpureus (10 cfu/ml) was co-cultured with various concentrations of E. burtonii (10M0 ) cfu/ral at three different feeding times (day 2, 4, and 6). Feeding times and concentrations of E. burtonii significantly increased production of lovastatin by four strains of M. purpureus (JMBA5K, AID, JMBA and TOS). The highest production of lovastatin was achieved by M. purpureus TOS co-cultured by E. burtonii at 10 cfu/ml added at day 6. Expression of the genes that responsible for lovastatin production were analyzed by PCR and RT-PCR method. The phenotypic character of M. purpureus TOS with high lovastatin production was conformed by the high intensity of its gene expression.